Metachronous triple cancers of the stomach, duodenum and rectum in a patient with familial adenomatous polyposis. Issue 11 (15th November 2022) - Uchiyama, Shuichiro; Ikeda, Naotaka; Oyama, Tomohiro; Eguchi, Mayumi; Sato, Rikiya; Ito, Ayaka; Toyosaki, Ryouichi; Kitazono, Masaki; Suenaga, Toyokuni
Abstract: Familial adenomatous polyposis (FAP) is an autosomal dominant disorder characterized by the presence of at least 100 adenomatous polyps in the colon and rectum. The risk of upper gastrointestinal tumors is relatively high in patients with FAP, but a case of triple cancers has not been reported in the literature. We herein report a case of metachronous triple cancers of the stomach, duodenum and rectum in a patient with FAP.